2010
DOI: 10.1177/1744987110387484
|View full text |Cite
|
Sign up to set email alerts
|

Graduate nurses’ and midwives’ perceptions of research

Abstract: An increasing amount of quantitative research has shown that nurses face considerable organisational and motivational barriers to conducting research. However, there is comparatively little qualitative information offering more detailed and subjective information about the research experiences of graduate nurses. The aim of this research was to explore graduate nurses' perceptions of the nursing research and development (R&D) culture in one health trust in the United Kingdom (UK). The research was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…The only statistically significant finding was that those enrolled in postgraduate degrees were more likely to report current involvement in a research project as a partial requirement of their degree. Other research has shown that graduate nurses (nurses with university degrees) perceive fewer barriers to research and have positive views concerning involvement in research compared to nurses with no graduate degrees (Snelgrove & James 2011). In addition, nurses with a higher level of education, in comparison with less educated peers, use research findings more frequently in practice (Veeramah 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only statistically significant finding was that those enrolled in postgraduate degrees were more likely to report current involvement in a research project as a partial requirement of their degree. Other research has shown that graduate nurses (nurses with university degrees) perceive fewer barriers to research and have positive views concerning involvement in research compared to nurses with no graduate degrees (Snelgrove & James 2011). In addition, nurses with a higher level of education, in comparison with less educated peers, use research findings more frequently in practice (Veeramah 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of communication about support available within organizations was also a barrier to research participation (Roxburgh 2006). Other studies of generalist nurses in the UK and USA suggest that family life and work balance was more of a priority for the participant's use of their time and that lack of time, organizational structures, and cultural differences posed significant barriers which diminished motivation, confidence, knowledge, and engagement with research (Snelgrove & James 2011). Other barriers to research that have been frequently reported are lack of research funding and education to become research ready (Darbyshire 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses frequently report that great personal motivation and personal sacrifices are necessary to integrate clinical research into their professional role. Research activities are often on one's own time, in addition to other professional responsibilities [7,11]. Two related themes were that of nurses' lack of ownership in the research in which they participate and the lack of dissemination of results of nursing research.…”
Section: Literature Review Barriers To Nursing Researchmentioning
confidence: 99%
“…Whilst the internship has been successful, the challenges identi ed need to be addressed. In particular, the challenge of supporting research activity in a clinical environment that often devalues such enterprises has long be recognised, particularly for Nurses and Allied Health Professionals [28].…”
Section: Discussionmentioning
confidence: 99%